Completeness of Methicillin-Resistant Staphylococcus aureus Bloodstream Infection Reporting From Outpatient Hemodialysis Facilities to the National Healthcare Safety Network, 2013. (11th November 2015) - Nguyen, Duc B.; See, Isaac; Gualandi, Nicole; Shugart, Alicia; Lines, Christi; Bamberg, Wendy; Dumyati, Ghinwa; Harrison, Lee H.; Lesher, Lindsey; Nadle, Joelle; Petit, Susan; Ray, Susan M.; et al.
Abstract : Reports of bloodstream infections caused by methicillin-resistant Staphylococcus aureus among chronic hemodialysis patients to 2 Centers for Disease Control and Prevention surveillance systems (National Healthcare Safety Network Dialysis Event and Emerging Infections Program) were compared to evaluate completeness of reporting. Many methicillin-resistant S. aureus bloodstream infections identified in hospitals were not reported to National Healthcare Safety Network Dialysis Event. Infect. Control Hosp. Epidemiol. 2016;37(2):205–207